#### Answer

(a) -3
(b) -45

#### Work Step by Step

We are given:
$f(x)=2x-3$ and $g(x)=4-x^2$
We evaluate:
(a) $(f\circ g)(-2)=f(g(-2))=f(4-(-2)^{2})=f(4-4)=f(0)=2(0)-3=0-3=-3$
(b) $(g\circ f)(-2)=g(f(-2))=g(2(-2)-3)=g(-4-3)=g(-7)=4-(-7)^{2}=4-49=-45$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) -3
(b) -45

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.